Reconstruction of the Naso-orbital-ethmoid (NOE) Complex Using the Osteocutaneous Radial Forearm Flap (OCRFF). (May 2015) - Cannady, Steven B.; Friedman, Oren; Chalian, Ara A.; Newman, Jason G.; Cook, Ted; Wax, Mark K.
Objectives: Describe the utility of osteocutaneous forearm flaps in reconstruction of naso-orbito-ethmoid (NOE) defects. Study Design: Case series with chart review. Setting: Tertiary medical centers. Subjects and Methods: The study was conducted on patients treated between the years 2000 and 2014 undergoing NOE resection with reconstruction using the radial forearm flap. Decision making, technical feasibility, need for revisions, and patient disease outcomes were included to assess the durability of reconstruction over remaining survival period. Results: Fifteen patients underwent NOE reconstruction in the timeframe studied. Five recent patients reported poor nasal airway but no diplopia or immediately clinically evident enopthalmus after NOE reconstruction in mean follow-up of 17.3 months. One-third of patients succumbed to disease in the study period, 3 without revision, and all but 2 surviving patients required revisions. Conclusion: Osteocutaneous radial forearm flap (OCRFF) is a cosmetically acceptable method of reconstructing NOE defects. Though a 1-step reconstruction can be serviceable without multiple additional procedures, longer surviving patients frequently receive revision surgery as with more traditional planned staged procedures.